Energy and exergy analysis of proposed compression-absorption refrigeration assisted by a heat-driven turbine at low evaporating temperature. (1st July 2019) - Chen, Wei; Li, Zoulu; Sun, Qiang; Zhang, Bin
Highlights: Only driven by heat, the proposed CRHT system can provide cooling at −60 °C. The proposed CRHT system were modeled by steady state and numerically simulated. Thermal performances of CRHT are better than those of TAR and HACR systems. Effects of T GEN, T 10, ω 4, and γ on thirteen key operating parameters were studied. The exergy flow schematic of CRHT system was drawn and analyzed in detail. Abstract: The thermal performances of proposed compression-absorption refrigeration assisted by a heat-driven turbine (CRHT) at low evaporating temperature were numerically investigated. According to the ideal isentropic process and the isentropic efficiency, the mathematical models of the micro tube and the compressors are built up. The CRHT system was modeled and simulated by considering the mass conservation, energy conservation, mechanical power conservation, and exergy generation equation of each component. For the case of basic design, the operating parameters, energy balance and the total thermal conductance of each component are calculated and analyzed. The effects of generation temperature, evaporating temperature of R134a, ammonia mass fraction of NH3 /H2 O, and compression ratios on thirteen key operating parameters were simulated and discussed. The COP of the CRHT system is compared with those of the two-stage absorption refrigeration system and the heat-driven compression-absorption refrigeration system in literatures, which proves that the proposed CRHT system possesses the best thermal performance. The exergy losses of each component were calculated and compared. It is indicated that the heat transfer areas of components should be optimized appropriately.